Factor that influenced awareness on retirement planning the case study in Cekap Technical Services Sdn Bhd / Nurbaiti Saniah Abdullah Shafari - Abdullah Shafari, Nurbaiti Saniah (Faculty of Business and Management, 2015)
This research is to study factors which are knowledge about retirement planning, goal clarity and potential conflict in retirement that influence awareness retirement planning. This research helps to determine that factors that influence awareness on retirement planning. 86 questionnaires were distributed to all employees in Cekap Technical Services Sdn Bhd. In order to analyzed finding of the data in the questionnaire, researcher was used Statistical Package for Social Science (SPSS) version 20.0 in order to find out reliability, frequency, descriptive, Pearson Correlation and Multiple Regression.